Cerium(IV) oxide: Synthesis in alkaline and acidic media, characterization and adsorption properties - Brigante, Maximiliano Eduardo (2012)
Cerium(IV) oxide or ceria materials were synthesized in alkaline and acidic media, using cerium(IV) sulfate as ceria precursor and cetyltrimethylammonium tosylate as template, in order to evaluate the effect of pH on the morphology and texture of synthesized materials. The results show that the surface area, the pore size and volume, and the surface charge can be tuned by changing the pH. Both ceria materials are formed by nanoparticles although in the material synthesized in acidic media (CeO 2(B)) the particles tend to form an ordered mesoporous structure with a narrower porous size distribution, mainly due to the formation of voids between them. CeO 2 material synthesized in alkaline media (CeO 2(A)), on the contrary, shows an irregular distribution of the pores with different sizes, which were probably formed by the stacking of ceria particles. These differences seem to be also attributed to the interaction between CTAT and ceria nanoparticles during the synthesis at both experimental conditions. The grain size, the surface area, the porous volume, and the isoelectric point of the synthesized materials were 8.5nm, 33.52m 2g -1, 0.06cm 3g -1, and 4 for CeO 2(A), respectively; and 13.4nm, 21.98m 2g -1, 0.05cm 3g -1, and 7.4 for CeO 2(B), respectively. Adsorption studies of synthesized materials toward tetracycline and minocycline antibiotics were performed and discussed. © 2012 Elsevier B.V.